2006
DOI: 10.1007/s00213-006-0427-y
|View full text |Cite
|
Sign up to set email alerts
|

A role for corticotropin-releasing factor, but not corticosterone, in acute food-deprivation-induced reinstatement of heroin seeking in rats

Abstract: The present data suggest that, as demonstrated for footshock-induced reinstatement of drug seeking, brain CRF, but not corticosterone, plays a critical role in acute food-deprivation-induced reinstatement of heroin seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 56 publications
4
39
2
1
Order By: Relevance
“…This is consistent with reports that acute stress-induced increases in corticosterone are not necessary for reinstatement following cocaine or heroin SA (Shaham et Erb et al, 1998;Shalev et al, 2006). These findings parallel clinical reports that although drug-, cue-and stress-induced drug craving are accompanied by activation of the HPA axis (Berger et al, 1996;Ward et al, 1999;Sinha et al, 2003), pharmacological inhibition of glucocorticoid secretion has little or no effect on evoked craving in cocaine-dependent individuals (Harris et al, 2004;Winhusen et al, 2005).…”
Section: Role Of Glucocorticoids In Stress-and Crf-induced Reinstatementsupporting
confidence: 90%
“…This is consistent with reports that acute stress-induced increases in corticosterone are not necessary for reinstatement following cocaine or heroin SA (Shaham et Erb et al, 1998;Shalev et al, 2006). These findings parallel clinical reports that although drug-, cue-and stress-induced drug craving are accompanied by activation of the HPA axis (Berger et al, 1996;Ward et al, 1999;Sinha et al, 2003), pharmacological inhibition of glucocorticoid secretion has little or no effect on evoked craving in cocaine-dependent individuals (Harris et al, 2004;Winhusen et al, 2005).…”
Section: Role Of Glucocorticoids In Stress-and Crf-induced Reinstatementsupporting
confidence: 90%
“…It is well established that the activation of central CRF system is essential for stress-induced reinstatement of drug-seeking behavior (Shaham et al, 1997;Le et al, 2000;Shalev et al, 2006), and CRF receptor antagonism blocks this stress effect (Shaham et al, 1998). Identifying the BNST as a key structure for mediating this phenomenon, Erb and Stewart reported that stress-induced reinstatement of drugseeking behavior is mimicked by an intra-BNST injection of CRF and blocked by an intra-BNST injection of a CRF antagonist, D-Phe CRF (Erb and Stewart, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As animal models have clearly demonstrated, CRFR1 antagonists are effective in attenuating stress-induced relapse to drug taking (76,(82)(83)(84). CP-154,526, a CRFR1 nonpeptide antagonist, attenuates stress-induced relapse to drug seeking in rats (77).…”
Section: Therapiesmentioning
confidence: 99%